Application of classical numerical methods in the calculation of solidification modes of a continuous ingot - V. I. Timoshpolsky; E. I. Marukovich; I. A. Trusova (Литьë и металлургия, 2020)
This paper presents approaches to the computational analysis of solidification and cooling processes of continuously cast billets in order to improve and develop technological modes in the conditions of modern continuous casting machines using FEM.The application of modern numerical methods for solidification and cooling of workpieces on continuous casting machines is considered. The use of the finite element method is justified when using computational and experimental data for the development and improvement of casting technology.